2015
DOI: 10.1016/j.dhjo.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

“How did that happen?” Public responses to women with mobility disability during pregnancy

Abstract: Background Little is known about current societal attitudes toward women with significant mobility disability who are visibly pregnant. Objective To use qualitative descriptive analysis methods to examine perceptions of women with significant mobility disability about how strangers reacted to their visible pregnancies. Methods In late 2013, we conducted 2-h telephone interviews with 22 women with significant mobility difficulties who had delivered babies within the prior 10 years. The semi-structured, open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 21 publications
0
33
0
7
Order By: Relevance
“…The resulting lack of clinicians’ knowledge puts WWPD at higher risk during pregnancy than women without disabilities. Many of these women are at higher risk for complications of pregnancy than other women because of complex health issues related to their disability (Iezzoni, Yu et al, 2014, 2015; Mitra et al, 2016a; Signore, Spong, Krotoski, Shinowara, & Blackwell, 2011). Although some of the issues identified by the women in this study may also occur in women without disabilities, the WWPD who participated specifically addressed the issues within the context of having a physical disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting lack of clinicians’ knowledge puts WWPD at higher risk during pregnancy than women without disabilities. Many of these women are at higher risk for complications of pregnancy than other women because of complex health issues related to their disability (Iezzoni, Yu et al, 2014, 2015; Mitra et al, 2016a; Signore, Spong, Krotoski, Shinowara, & Blackwell, 2011). Although some of the issues identified by the women in this study may also occur in women without disabilities, the WWPD who participated specifically addressed the issues within the context of having a physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the passage of the Americans with Disabilities Act 25 years ago, individuals with disabilities, including those with physical disabilities, continue to experience barriers to health care (Peacock, Iezzoni & Harkin, 2015); the negative effects of these barriers extend to pregnant women with physical disabilities. A growing body of research has demonstrated that women with disabilities have unmet needs and experience complications related to pregnancy and childbearing that are uncommon in women without disabilities (Iezzoni, Yu, Wint, Smeltzer, & Ecker, 2014, 2015; Mitra, Clements, Zhang, & Smith, 2016a; Mitra, Long-Bellil, Iezzoni, Smeltzer, & Smith, 2015). Women with physical disabilities (WWPD) reported negative attitudes toward them from acquaintances as well as strangers (Iezzoni, Wint, Smeltzer, & Ecker, 2015a; Nosek, Rintala, Howland, Foley, & Bennett, 1995).…”
mentioning
confidence: 99%
“…Fiziksel engelli olmasına rağmen, ebeveyn olmak ve çocuk yetiştirmek isteyen kadın sayısı da artmıştır (Başgöl ve Oskay, 2015;Timur vd., 2006;Iezzoni et al, 2015).…”
Section: Introductionunclassified
“…Bu görmezden gelmenin başlıca nedenlerinden biri konuyla ilgili yeterli bilgi sahibi olunmamasıdır (Başgöl ve Oskay, 2015;Timur vd., 2006;Iezzoni et al, 2015). Bu nedenle fiziksel engelli anne adayları doğum öncesi, doğum ve doğum sonrası dönemlerde çeşitli sorunlarla karşılaşmaktadırlar.…”
Section: Introductionunclassified
See 1 more Smart Citation